Implementation Android Based E-Commerce for Improving Business Process and Increasing Revenue - et.al, Fergyanto E. Gunawan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
E-commerce is one of the solutions to make a business known by people and gaining new customers. E-commerce makes transaction between seller and customer convenient because people no longer need to come to the store if they want to buy something. Retail Businesses that still serve their customers using old method or only serve the customers who come to the store will lose with the competitors that use e-commerce because many people right now using e-commerce in their smartphone to find the products they wanted rather than to go to the store and it makes the business can’t get any new customers and can’t increase their revenue. Retail Businesses needs to change their old method to a new one by using android based e-commerce. Android based e-commerce is designed using Extreme Programming method. The old method that the business used will be replaced into a new one where the business will serve the customers online by using android based e-commerce and also serve the customers who came to the store. The changes from implementing android based e-commerce is expected to make the business process in retail business will be more efficient and effective to increase revenue and customer’s satisfaction.